Perbedaan Pengaruh Enterprise Risk Management (ERM) terhadap Nilai Perusahaan Sebelum dan Semasa Covid-19 - Natasha Kamtoso; Melissa Evelyn Wijaya; Juniarti Juniarti (Business Accounting Review, 2021)
Enterprise Risk Management is an activity and strategy that allows a company to managevarious types of risks to increase the value of the company for its stakeholders. This study aims toexamine the positive relationship between ERM and firm value, as well as examine the moderatingrole of the Covid-19 pandemic in the relationship between ERM and firm value in the bankingsub-sector listed on the Indonesia Stock Exchange. The independent variable in this study isEnterprise Risk Management and the dependent variable in the study is firm value as measured byTobin's Q. This study uses 4 control variables, namely, ROA, leverage, firm size, and cash flow fromoperating. In addition, the Covid-19 pandemic is used as a moderator between ERM and companyvalue. The sample in this study is the banking sub-sector companies listed on the Indonesia StockExchange in the 2018-2021 period, which were selected using the purposive sampling method withthe final sample of 26 companies. Based on the results obtained, ERM proved to have a positiveeffect on firm value. Meanwhile, the Covid-19 pandemic has not proven to strengthen the positiverelationship between ERM and firm value.